Biological control of grapevine gray mold: in vitro and in vivo evaluation of the antagonistic activity of indigenous Trichoderma harzianum strains (Mascara, Algeria) - Benbahi, Imen; Merzoug, Aoumria; El Amine Kouadri, Mohamed; Bennacer, Amel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Gray mold, caused by the necrotrophic fungus Botrytis cinerea, was responsible for significant economic losses in grapevine (Vitis vinifera L.) production worldwide, including Algeria, which highlighted the need for sustainable control alternatives. The objective of this study was to evaluate the antagonistic potential of an indigenous Trichoderma harzianum strain against local B. cinerea isolates from Mascara, Algeria. A highly virulent B. cinerea isolate (BC3) was collected from infected grapevine leaves and identified through morphological and molecular analyses, while the antagonistic T. harzianum isolate (T5) was obtained from the rhizosphere of healthy vines. In vitro dual-culture assays showed that T. harzianum significantly inhibited the mycelial growth of B. cinerea, with direct inhibition of 80.50 % and indirect inhibition of 72.87 %. In vivo experiments further confirmed its efficacy, reducing disease incidence by 56.25 % and enhancing plant growth, increasing height from 60 to 96 cm with notable improvement in vegetative biomass. These findings suggested that the indigenous T. harzianum T5 strain was a promising and effective biocontrol agent for the sustainable management of gray mold in vineyard.